A systematic review of educational interventions to change behaviour of prescribers in hospital settings, with a particular emphasis on new prescribers. (10th January 2013) - Brennan, Nicola; Mattick, Karen
<x xml:space="preserve">Abstract</x> Aims Prescribing is a complex task and a high risk area of clinical practice. Poor prescribing occurs across staff grades and settings but new prescribers are attributed much of the blame. New prescribers may not be confident or even competent to prescribe and probably have different support and development needs than their more experienced colleagues. Unfortunately, little is known about what interventions are effective in this group. Previous systematic reviews have not distinguished between different grades of staff, have been narrow in scope and are now out of date. Therefore, to inform the design of educational interventions to change prescribing behaviour, particularly that of new prescibers, we conducted a systematic review of existing hospital‐based interventions. Methods Embase, Medline, SIGLE, Cinahl and PsychINFO were searched for relevant studies published 1994–2010. Studies describing interventions to change the behaviour of prescribers in hospital settings were included, with an emphasis on new prescibers. The bibliographies of included papers were also searched for relevant studies. Interventions and effectiveness were classified using existing frameworks and the quality of studies was assessed using a validated instrument. Results Sixty‐four studies were included in the review. Only 13% of interventions specifically targeted new prescribers. Most interventions (72%) were deemed effective in changing behaviour but no particular type stood out as most effective. Conclusion Very few studies have tailored educational interventions to meet needs of new prescribers, or distinguished between new and experienced prescribers. Educational development and research will be required to improve this important aspect of early clinical practice.